Hubungan Antara Kehamilan Isteri Dengan Perubahan Perilaku Suami Di Desa Menganti Kabupaten Cilacap - Agus Darwanto (Politeknik Karya Husada, 2022)
Pregnancy of pregnant women is often associated with various myths circulating in society. Several myths turned out to influence the behavior of the man who became her husband. The purpose of this study was to examine the correlation between a woman's pregnancy and changes in the husband's behavior. The research method used is descriptive quantitative. Collected data by conducting observations, interviews, and surveys using questionnaires and documentation. Sampling method using random sampling. Data analysis used descriptive analysis with cross-tabulation and linear regression. The results showed that the level of trust of men in Menganti village was not that high, but the attitude of doubt and feeling worried if there was a bad impact on the child who was still in the womb of his wife was still quite high. The results of linear regression show that there is a correlation between the wife's pregnancy and her husband's behavior with a correlation rate of 57.6% (medium) and an influence level of 33.2% (low).